Maternal health : cost analysis of introducing the Umbiflow Velocity Doppler System at primary health level : a pilot study conducted at Kraaifontein Community Health Centre and Durbanville Day Clinic - Chiwire, Plaxcedes (Health Economics Unit, 2016)
Background: A South African report, Saving Babies 2010-2011, reports 32,178 still births in a 2 year period of January 2010 to December 2011 within the 94% of the total hospitals who provide data to a Perinatal Problem Identification programme (PPIP). In order to deal with perinatal mortality, specifically Intra-Uterine Growth there is needed to equip the primary health care (PHC) with technology for monitoring. An instrument called the Umbiflow Doppler ultrasound machine has been developed and there is need to test its economic impact in the PHC. Methods: A cross- sectional analytical study was conducted in the Tygerberg Eastern Health District of the Metro Region of Western Cape, South Africa at two primary health care (PHC) facilities, one secondary level hospital, and one tertiary hospital namely Kraaifontein Community Health Centre (CHC), Durbanville Day Clinic, Karl Bremmer District Hospital, and Tygerberg Hospital respectively. The aim of the research was to conduct a cost analysis in the introduction of an Umbiflow Doppler machine in the primary health care with the major goal being to reduce the number of perinatal deaths in the public health system. A societal perspective was adopted. The cost analysis study was carried out on the already approved sample size of 139 patients stemming from the Umbiflow Clinical study. The inclusion criteria for patient participation was poor SF growth and late bookers >28 weeks attending Kraaifontein Community Health Care Centre and Durbanville Clinic for antenatal services.